2018
DOI: 10.1002/nag.2801
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of the hydrofracturing behaviour of heterogeneous glutenite considering hydro‐mechanical coupling effects based on bonded particle models

Abstract: The heterogeneity of tight reservoirs significantly influences hydrofracturing behaviours, such as crack morphology, type, initiation, propagation, and distribution. The accurate characterisation of the influencing mechanisms has become a pivotal issue in enhancing the fracturing stimulation of tight reservoirs, as well as in the prediction of tight oil and gas production. In this study, the hydrofracturing behaviours of heterogeneous glutenites and their influencing mechanisms were numerically investigated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…Zhang [26] investigated the influence of F 0 variation on macro-permeability and pore pressure and then established a weak structural plane to form three different models of hydraulic crack contact with the weak structural plane. Yang [27] constructed a 3D model of heterogeneity of cylindrical sandstone samples through CT scanning, and then reconstructed it in 3D based on the bonded-particle model (BPM). Through a series of numerical simulations, they showed that heterogeneous sandstone particles inhibit crack growth.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [26] investigated the influence of F 0 variation on macro-permeability and pore pressure and then established a weak structural plane to form three different models of hydraulic crack contact with the weak structural plane. Yang [27] constructed a 3D model of heterogeneity of cylindrical sandstone samples through CT scanning, and then reconstructed it in 3D based on the bonded-particle model (BPM). Through a series of numerical simulations, they showed that heterogeneous sandstone particles inhibit crack growth.…”
Section: Introductionmentioning
confidence: 99%
“…The brittleness and fracability of glutenite are affected not only by the mechanical properties of matrix, but also by gravel size and volume content, and mechanical properties of different rock structures. Fracture propagation behavior and the hydraulic fracturing effect of glutenite reservoirs are controlled by mechanical properties [15,55,56], geological conditions [57][58][59][60], and technical parameters [60][61][62]. The effect of glutenite brittleness on hydraulic fracture propagation mechanisms and fracturing needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…separation of elements). Using CDEM, Ju et al [159,160,162] studied 2D and 3D propagation of hydraulic fractures in heterogeneous glutenite, where the gravels and natural fractures captured using CT-scan are incorporated into the numerical models and show non-negligible influence on the fracture path.…”
Section: Hybrid Continuum/discontinuum-based Methodsmentioning
confidence: 99%
“…More recently, CT-scan techniques have been increasingly used in experiments to detect natural fractures and stimulated hydraulic fracture network [40,125,162,196,198,397]. Liu et al [196] identified 3D propagation and distribution of hydraulic fractures in heterogeneous rocks and found the rock heterogeneity and horizontal in situ stress ratio have a significant influence on the stimulated fracture network.…”
Section: Interaction Of Hydraulic and Natural Fracturesmentioning
confidence: 99%